جمع عثمانی اور جمع صدیقی کے درمیان بنیادی فرق کے تناظر میں بعض اشکالات کا جائزہ: An Analysis of Certain Issues in the Light of the Fundamental Differences Between the ʿUthmānic and Ṣiddīqī Compilations of the Qur’an - Aslam siddique, Dr. Muhammad Aslam (MEI, 2025)
Orientalists have attempted to cast doubt on the authenticity of the ʿUthmānic Codex by asserting that the Ṣuḥuf Ṣiddīqiyyah was not a fully organized manuscript and that the ʿUthmānic Muṣḥaf was merely its copy—implying that if the former lacked reliability, the latter could not be authoritative. Some Muslim scholars further argue that Abū Bakr’s goal was textual preservation, while ʿUthmān’s aim was to preserve the qirāʾāt (modes of recitation). Another suspicion raised is that if the Qur’an was recompiled during ʿUthmān’s time, it suggests that the Companions did not fully trust the earlier compilation. Through careful analysis of historical sources, this study establishes that the ʿUthmānic codices were primarily based on the Ṣuḥuf Ṣiddīqiyyah prepared during the caliphate of Abū Bakr al-Ṣiddīq (RA), with only minor differences between the two. The first compilation was prompted by fear that portions of the Qur’an might be lost after the martyrdom of many ḥuffāẓ, while the ʿUthmānic recension aimed to resolve disputes among non-Arab Muslims regarding qirāʾāt. In the first compilation, the Qur’an was collected on separate sheets (ṣuḥuf); verses were arranged in order, though sūrahs were not yet compiled into one bound volume. These ṣuḥuf were written according to the ʿarḍah ākhirah (final presentation before the Prophet ﷺ) and encompassed all seven aḥruf. When Caliph ʿUthmān (RA) undertook the second compilation, he used these ṣuḥuf as the main source, arranging the sūrahs sequentially and producing a unified codex in a standardized script that accommodated the seven aḥruf verified in the ʿarḍah ākhirah. Thus, the Muṣḥaf ʿUthmānī was a meticulous reorganization of the Ṣuḥuf Ṣiddīqiyyah, with deliberate preference for the Quraysh dialect to ensure uniformity across authentic recitations. The first compilation safeguarded the Qur’an under collective supervision, while the ʿUthmānic project unified the Muslim community upon a single authoritative text—based on the ʿarḍah ākhirah and authentic qirāʾāt—by producing and dispatching multiple official copies across the Islamic world.